Evaluating biomarkers in canine cytotoxic interface dermatitis reactions to account for clinical and histopathological similarities and differences - Kannan, Shriya; Wong, Neil B.; Ryan, Grace E.; James, Nia E. R.; Ajayi, Ayodeji; Lubov, Janet E.; David, Clement N.; Wrijil, Linda; Robinson, Nicholas A.; Hughes, Kelly; Almela, Ramon M.; Richmond, Jillian M. (Frontiers in Veterinary Science, 2025)
Cytotoxic interface dermatitis (CID) is a pattern reaction predominantly at the dermo-epidermal junction that encapsulates numerous chronic non-communicable inflammatory skin conditions in which the basal keratinocytes are attacked by T-cell infiltrate leading to apoptosis, lymphocytic satellitosis and vacuolar degeneration. Though many diseases include CID, the type of clinical presentation and tissue patterns expressed from disease to disease varies. In this study, we evaluate the commonalities and discrepancies in significantly expressed biomarkers across several CID conditions to examine their impact on clinical presentations in canines. Among the uniquely expressed genes in each disease, we observed significantly expressed IFNG in Discoid Lupus Erythematosus, TRAT1 in Epitheliotropic Lymphoma, and CXCL8 and CSF3R in pemphigus affected dogs. With this knowledge, we may be able to use molecular signatures in combination with current treatment practices to develop a more targeted treatment plan for patients with CID.